Arthroscopic Management of Intraarticular Screw Perforation after Surgical Treatment of an Acetabular Posterior Wall Fracture: A Case Report - Jang, Jae Hoon (Hip Pelvis, 2018)
Although surgical techniques for treating acetabular fracture are evolving, the use of periacetabular screws is common, and their placement in acetabular surgery is still technically demanding. For instance, intraarticular screw perforation is a serious complication that may occur during surgical treatment of an acetabular fracture. Here, we describe the case of a 50-year-old female who experienced an intraarticular screw perforation after surgical treatment of a posterior acetabular wall fracture. Removal of the perforated screw was performed arthroscopically based on its ability to offer minimally invasive access to the hip joint. One year after removal of the screw, no radiological signs of osteoarthritic changes were observed. The patient regained normal ambulation without limitations to range of motion or hip pain. To our knowledge, this is the first report on the use of arthroscopy to treat intraarticular screw perforation after surgical treatment of an acetabular fracture.